Effects of warming and nitrogen addition on soil fungal and bacterial community structures in a temperate meadow - Jiang, Ming; Tian, Yibo; Guo, Rui; Li, Shuying; Guo, Jixun; Zhang, Tao (Frontiers in Microbiology, 2023)
Soil microbial communities have been influenced by global changes, which might negatively regulate aboveground communities and affect nutrient resource cycling. However, the influence of warming and nitrogen (N) addition and their combined effects on soil microbial community composition and structure are still not well understood. To explore the effect of warming and N addition on the composition and structure of soil microbial communities, a five-year field experiment was conducted in a temperate meadow. We examined the responses of soil fungal and bacterial community compositions and structures to warming and N addition using ITS gene and 16S rRNA gene MiSeq sequencing methods, respectively. Warming and N addition not only increased the diversity of soil fungal species but also affected the soil fungal community structure. Warming and N addition caused significant declines in soil bacterial richness but had few impacts on bacterial community structure. The changes in plant species richness affected the soil fungal community structure, while the changes in plant cover also affected the bacterial community structure. The response of the soil bacterial community structure to warming and N addition was lower than that of the fungal community structure. Our results highlight that the influence of global changes on soil fungal and bacterial community structures might be different, and which also might be determined, to some extent, by plant community, soil physicochemical properties, and climate characteristics at the regional scale.